Analysis of Mathematics and Creative Science Learning in Early Childhood Al-Kausar Perjuangan Kindergarten - Safitri, Inayatu (Seulanga : Jurnal Pendidikan Anak, 2024)
This study aims to analyze the implementation of mathematics and creative science learning in early childhood education at Al-Kausar Perjuangan Kindergarten. Mathematics learning focuses on introducing numbers and developing counting skills, while science learning emphasizes color recognition and environmental understanding through indoor and outdoor experiments. This research employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The findings reveal that creative integration of mathematics and science through play-based activities enhances children’s curiosity, logical thinking, and problem-solving abilities. Activities such as rainbow experiments, gardening, tug-of-war, arranging bottle caps, storytelling, watercolor exploration, singing, and making picture frames from ice cream sticks effectively foster motivation and support cognitive, motor, and social development. These engaging and meaningful learning experiences help children gain a deeper understanding of basic mathematical and scientific concepts while maintaining enjoyment in the learning process. The study concludes that implementing creative, contextual, and play-oriented strategies is essential to stimulate interest, encourage active participation, and strengthen the foundation of mathematical and scientific literacy in early childhood education.